Increased expression of lncRNA FTH1P3 predicts a poor prognosis and promotes aggressive phenotypes of laryngeal squamous cell carcinoma. Issue 6 (18th June 2019) - Yuan, Haozhan; Jiang, Hong; Wang, Yanting; Dong, Yameng
Abstract : Laryngeal squamous cell cancer (LSCC) is a highly aggressive malignancy in the head and neck region. Recent studies have shown that long noncoding RNAs (lncRNAs) are novel transcripts that play an important role in the progression of LSCC. However, the overall pathophysiological regulation of lncRNAs to LSCC is largely unknown. The present study aimed to determine the clinical significances of lncRNA ferritin heavy chain 1 pseudogene 3 (FTH1P3) and to identify its potential roles in LSCC. Quantitative real-time PCR (qRT-PCR) showed that FTH1P3 expression was significantly up-regulated in LSCC tissues than that in non-neoplastic tissues. High FTH1P3 expression was positively correlated with the poor differentiation, high T classification, positive lymph node metastasis, and advanced clinical stage. Overall survival analysis showed that high levels of FTH1P3 predicted a poor prognosis in LSCC patients. Moreover, elevated expression of FTH1P3 was found to increase LSCC cell proliferation, migration and invasion, and to inhibit cell apoptosis, Conversely, knockdown of FTH1P3 suppressed LSCC cell proliferation, migration and invasion, and induced cell apoptosis. In addition, overexpression of FTH1P3 resulted in an increase in cells in S phase and a decrease in cells in G0/G1 phase, whereas inhibition of FTH1P3 did the opposite effects. Taken together, these results suggested that increased expression of FTH1P3 predicts a poor prognosis and promotes aggressive phenotypes of LSCC by regulating cell proliferation, migration, invasion, apoptosis, and cell cycle, indicating FTH1P3 may serve as a promising therapeutic biomarker for the treatment of LSCC.